The complex interaction between channel–levee systems and mass transport complexes in the Pliocene–Quaternary Rakhine Basin, offshore Myanmar - Shao, Dali; Fan, Guozhang; Ma, Hongxia; Wang, Haiqiang; Ding, Liangbo; Zuo, Guoping; Lu, Yintao; Xu, Xiaoyong (Frontiers in Earth Science, 2024)
Channel–levee systems (CLSs) and mass transport complexes (MTCs) are prevalent in deep-water basins, yet their interplay remains enigmatic. This study uses high-resolution 3D seismic data to investigate the architecture of CLSs and MTCs, aiming to explore how CLSs influence the distribution of MTCs in the Rakhine Basin, Bay of Bengal. Two models are built to illustrate the interaction between CLSs and MTCs. In the first model, large-scale aggradational CLSs created unfilled relief in their overbank environments, which acted as spatially confined topography for subsequent mass-wasting deposits. In this model, the interaction between large-scale CLSs and confined MTCs controls the distribution of confined MTCs. In the second model, laterally migrating CLSs do not create such prominent topographic relief in their overbank environments. This characteristic renders them inconsequential in influencing the distribution of subsequent mass-wasting processes. Consequently, spatially extensive MTCs develop within unconfined settings. This configuration gives rise to lithological traps, which might be common and represent potential drilling targets on continental margins. This study could contribute to a better understanding of the interplay between CLSs and MTCs and have some enlightenment on looking to provide some insight into the search for lithological traps in the Rakhine Basin.